Leadership Capability Framework for the Construction Industry Leaders in Malaysia - Nadrah, Wan Hanim Binti Wan Muda; Libunao, Wilfredo Herrera; Isa, Khairunesa; Ahmad, Abd Rahman; Yusoff, Rosman Md. (International Journal of Engineering and Technology, 2018)
This study aims to identify the leadership capabilities for Malaysia construction industry team leaders. This research apllied exploratory sequential mix-method research design where is qualitative followed by quantitative method. In the first phase, semi-structured interview was used and purposive sampling was employed in selecting 15 research participants. Team leaders and Human Resource Managers were selectetd to be reseach participants of this study. Qualitative data was analysed using content and thematic analyses. Quantitative data was collected using survey questionnaire involving 171 randomly selected team leaders as respondents. The data was examined using descriptive and inferential statistics consisting of t-test, One-way Analysis of Variance (ANOVA), Pearson Correlation, Multiple Regression and Structured Equation Modeling (SEM). This research found that personal integrity, working within industry, customer focus and quality, communication and interpersonal skill, developing and empowering people and working as a team were required leadership capabilities among construction industry team leaders. Findings also indicated that leadership skills was the important element to develop leadership capability. A framework developed can be used as a guide by employers in improving leadership capability of Malaysia construction industry team leaderÂ .